Molecular van der Waals Space and Topological Indices from the Distance Matrix - Ciubotariu, Dan (Molecules, 2004)
A comparative study of 36 molecular descriptors derived from the topological distance matrix and van der Waals space is carried out within this paper. They are partitioned into 16 generalized topological distance matrix indices, 11 topological distance indices known in the literature (seven obtained from eigenvalues/eigenvectors of distance matrix), and 9 van der Waals molecular descriptors. The generalized topological distance indices, (k)δ(λ) (λ = 1 – 3, k = 1 – 4), are introduced in this work on the basis of reciprocical distance matrix. Intercorrelation analysis reveals that topological distance indices mostly contain the same type of information, while van der Waals indices can be bound to the shape or the size of molecules. Furthermore, we found that topological distance indices are good for describing molecular size, and they may be viewed as bulk parameters. The most accurate QSPR models for predicting boiling point of alkanes are based on some of the generalized, eigenvalues/eigenvectors topological distance indices and the van der Waals descriptors of molecular size.